Donor Perspectives on Accountability and Transparency of Nonprofit Financial Reporting - Amartha, Pandu; Hamzani, Umiaty; Yantiana, Nella (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The number of cases involving the misappropriation of donation funds given by the public to nonprofit organizations has garnered significant attention. One common issue is the ethics surrounding donation solicitation. The methods often used by certain individuals include the inaccuracy of information provided by nonprofit organizations to donors, leading to subpar services and misallocation of funds that do not align with the donation values. This research aims to reveal donors' understanding of the transparency of funds managed by nonprofit organizations, as well as their trust in how donation funds are administered. Additionally, it seeks to uncover donors' perspectives on accounting practices and the transparency of financial reports within nonprofit organizations. This study is qualitative and employs a descriptive method. Data collection was conducted through interviews and open-ended questionnaires. The data obtained were subsequently analyzed. The results indicate that donors' views on the accountability of financial reporting by nonprofit organizations in Pontianak are quite positive, as evidenced by seven accountability indicators. However, the perception of donors regarding the transparency of financial reporting in these organizations is still lacking.